Bukti Peran Perilaku Keuangan Sebagai Pemediasi dalam Literasi Keuangan, Risk Tolerance dan Keputusan Investasi - Sherli Wahyuni Dwi Afriani; Isnurhadi Isnurhadi; Yuliani Yuliani (Jurnal Manajerial, 2023)
Background – The importance of planning in making investment decisions makes a person more mature in determining investment decisions to achieve financial well-being in the future. The realization of good investment decisions depends on appropriate financial instruments to invest in to maximize their use Aim – The purpose of this research is to determine the effect of Financial Literacy and Risk Tolerance on Investment Decisions mediated by Financial Behavior Design / methodology / approach – This research uses a quantitative approach and is analyzed using SmartPLS. Data obtained by Slovin sampling technique by distributing questionnaires to 400 respondents. Findings – The results of this study indicate that Financial Literacy, Risk Tolerance and Financial Behavior have a positive and significant effect on Investment Decisions. Financial Literacy and Risk Tolerance have a positive and significant effect on financial behavior. Financial literacy has a significant positive effect on investment decisions mediated by Financial Behavior. Risk Tolerance has a significant positive effect on Investment Decisions mediated by Financial behavior. Conclusion – Investors with good financial literacy and risk tolerance and followed by good financial behavior will make investment decisions according to their risk profile and investment objectives. Research implication – This research is for investors to broaden their knowledge regarding the functions of financial literacy and risk tolerance so that they can minimize bad financial behavior and be able to think rationally in investment decisions Limitations – The limitations of this research only include the variables of financial literacy, risk tolerance, financial behavior and investment decisions